Documentation of clinical pharmacy interventions for the development of a competency based training program for clinical pharmacy in a medical center - Ricaforte, Hazel Faye (Nacu) 1970-
Clinical pharmacy practice has been in existence since 1974 in the selected Medical Center, a 700-bed, tertiary, training, private hospital, but there has been no system of documentation for pharmacy interventions and no specific training program for clinical pharmacists. This is a nine-month study from August 2002 to April 2003. In this study, a documentation system for pharmacy interventions was designed and implemented. Pharmacy interventions cover initiative during the prescribing stage (prescribing errors and prescribing omissions) and drug therapy monitoring stage of drug administration. The study found that the majority (prescribing errors 27% and prescribing omission 35%) of the interventions were initiated during the prescribing stage. Hence, medication errors are intercepted at the earliest stage of drug administration. The acceptance rating of pharmacy interventions done is 98%. The study further supports the need for a pharmacist to review, analyze and interpret all doctors? orders prior to drug administration, especially in a training hospital. A training needs assessment survey was conducted, with the introduction of three modules in the training program: basic clinical pharmacy practice, application of clinical principles and drug therapy monitoring. Measurements of effectiveness of this program were based on increase in pharmacy interventions, increase in pre/post test results and increase in adverse drug reaction reports. After the training program paired sample t-test result shows that there is a significant increase in the number of pharmacy interventions (t=8.371, p=0.000), posttest results (t=12.911, p=0.000), and adverse drug reaction reports (t=2.760, p=≤0.010). Age is moderately correlated to the difference between pretest and posttest scores (r=0.583, p=0.000). Number of years as clinical pharmacists is also moderately correlated to the difference between pretest and posttest scores (r=0.546, p=0.001). Performance evaluation based on identified competencies showed that the highest competency rating is in providing emergency care (x=4.3, 5 being the highest) and the lowest rating is in monitoring drug therapy (x=3.6). Competencies that need further improvement were also identified: patient counseling and providing drug information.